Performance measurement of professional services: a case of Malaysia - Ali Khan, Mohd. Noor Azli (Penerbit UTM Press, 2009)
Performance measures allow companies to allocate economic responsibilities and decision rights, set performance targets, and reward target achievement (Merchant & Van der Stede, 2007). information for performance measurement and control can serve for decision-making, planning and control, signalling, education and learning, and external communication (Simons, 2000). Performance measurement and management refer to goal definition, strategy development, benchmarking, human resource management, and feedback processes of learning organizations (Otley, 1999). Performance measurement is an integral part of the planning and control cycle (Barnard, 1962) since a long time ago and managers must have been planning and controlling the deployment of resources since the first organization was established (Neely, 1999). the importance of performance measurement has been recognised and many frameworks have been developed such as Performance Measurement Matrix (Keigen et al., 1989), SMART (Cross & Lynch, 1989), Performance Measurement Questionnaire (Dixon et al., 1990) and Balance Scorecard (Kaplan & Norton, 1992). Furthermore, the Balance Scorecard is probably the best known of the raft of multi- dimensional performance measurement frameworks developed in the late 1980s and early 1990s (Bourne, 2008).